2017
DOI: 10.1007/s10555-017-9709-6
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylated alanine-rich C kinase substrate (MARCKS): a multirole signaling protein in cancers

Abstract: Emerging evidence implicates myristoylated alanine-rich C-kinase substrate (MARCKS), a major substrate of protein kinase C (PKC), in a critical role for cancer development and progression. MARCKS is tethered to the plasma membrane but can shuttle between the cytosol and plasma membrane via the myristoyl-electrostatic switch. Phosphorylation of MARCKS by PKC leads to its translocation from the plasma membrane to the cytosol where it functions in actin cytoskeletal remodeling, Ca signaling through binding to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 86 publications
1
70
0
1
Order By: Relevance
“…In this study, 3 genes ( NCS1 , SLC44A5 , and MARCKS ) were found to be coordinately controlled by both miR‐144‐5p and miR‐144‐3p in LUSQ cells. MARCKS is a major substrate of protein kinase C . Recent studies have shown that MARCKS plays a pivotal role in cancer development and progression .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, 3 genes ( NCS1 , SLC44A5 , and MARCKS ) were found to be coordinately controlled by both miR‐144‐5p and miR‐144‐3p in LUSQ cells. MARCKS is a major substrate of protein kinase C . Recent studies have shown that MARCKS plays a pivotal role in cancer development and progression .…”
Section: Discussionmentioning
confidence: 99%
“…27 In this study, 3 genes (NCS1, SLC44A5, and MARCKS) were found to be coordinately controlled by both miR-144-5p and miR-144-3p in LUSQ cells. MARCKS is a major substrate of protein kinase C. 42 Recent studies have shown that MARCKS plays a pivotal role in cancer development and progression. 42 Moreover, in lung cancer, aberrant MARCKS expression was detected in clinical specimens, and MARCKS expression was implicated in this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MARCKS is a membrane-bound protein that functions in various important cellular processes, such as cytoskeletal remodeling, motility, secretion and exocytosis [17]. For instance, MARCKS has been shown to regulate the actin cytoskeleton and, consequently, the number and length of filopodia [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, MARCKS has been shown to regulate the actin cytoskeleton and, consequently, the number and length of filopodia [18]. Interestingly, the phosphorylated form of MARCKS has been shown to promote cell motility and membrane protrusions and significantly affect the invasiveness of several cancer cells [17]. However, a possible functional role of the MARCKS protein in WNT5A-induced melanoma cell migration and invasion has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%